Dynamics of black hole–neutron star binaries in young star clusters. Issue 2 (10th July 2020) - Rastello, Sara; Mapelli, Michela; Di Carlo, Ugo N; Giacobbo, Nicola; Santoliquido, Filippo; Spera, Mario; Ballone, Alessandro; Iorio, Giuliano
ABSTRACT: Young star clusters are likely the most common birthplace of massive stars across cosmic time and influence the formation of compact binaries in several ways. Here, we simulate the formation of black hole–neutron star binaries (BHNSs) in young star clusters, by means of the binary population synthesis code MOBSE interfaced with the N -body code NBODY6++GPU . BHNSs formed in young star clusters (dynamical BHNSs) are significantly more massive than BHNSs formed from isolated binaries (isolated BHNSs): ∼40 per cent of the dynamical BHNS mergers have a total mass of >15 M⊙, while only ∼0.01 per cent of the isolated BHNS mergers have mass in excess of this value. Hence, our models strongly support a dynamical formation scenario for GW190814, given its total mass of ∼26 M⊙, if this event is a BHNS merger. All our dynamical BHNSs are ejected from their parent star cluster before they reach coalescence. Thus, a significant fraction of BHNS mergers occurring in the field might have originated in a young star cluster. The mass spectrum of BHNS mergers from gravitational-wave detections will provide a clue to differentiate between dynamical and isolated formation of BHNSs.